2012
DOI: 10.1136/bmjopen-2011-000647
|View full text |Cite
|
Sign up to set email alerts
|

The effect of MELatOnin on Depression, anxietY, cognitive function and sleep disturbances in patients with breast cancer. The MELODY trial: protocol for a randomised, placebo-controlled, double-blinded trial

Abstract: IntroductionBreast cancer represents about one-third of all cancer diagnoses and accounts for about 15% of cancer deaths in women. Many of these patients experience depression, anxiety, sleep disturbances and cognitive dysfunction. This may adversely affect quality of life and also contribute to morbidity and mortality. Melatonin is a regulatory circadian hormone having, among others, a hypnotic and an antidepressive effect. It has very low toxicity and very few adverse effects compared with the more commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 99 publications
0
31
0
2
Order By: Relevance
“…In a randomized controlled double-blind clinical trial on 50 patients referred for liver surgery a single preoperative enteral dose of 50 mg/kg melatonin was safe and well tolerated [215]. This underlines the urgent need for large clinical trials in the field of melatonin and cancer [216,217]. …”
Section: Resultsmentioning
confidence: 99%
“…In a randomized controlled double-blind clinical trial on 50 patients referred for liver surgery a single preoperative enteral dose of 50 mg/kg melatonin was safe and well tolerated [215]. This underlines the urgent need for large clinical trials in the field of melatonin and cancer [216,217]. …”
Section: Resultsmentioning
confidence: 99%
“…Among factors negatively affecting their quality of life, patients with breast cancer live with depression, anxiety, fatigue, pain, and sleep disorders, which may contribute to an increase in mortality. (6) In addition to a positive correlation between poor sleep quality and depression, there was a negative correlation between hope and poor sleep quality scores and, similarly, between hope and depression, in all stages of this study. Furthermore, health status, family support, and self-esteem of women with breast cancer have been shown to indirectly affect depression through hope.…”
Section: Discussionmentioning
confidence: 85%
“…(4,5) A complex relationship -under the influence of several factors -can be distinguished between depression and breast cancer, despite the former often being undiagnosed and untreated. (6) Depression and mood swings may present throughout treatment or even after its conclusion. (7,8) Depressive symptoms are predictors of subjective sleep quality in women with breast cancer before, during and after radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that melatonin has a possible anti-depressive, anxiolytic, analgesic or sedative effects, among others, probably based on its effect on the circadian functions regulation (Hansen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%